Why Did Holdings of Highly Rated Securitization Tranches Differ So Much across Banks? - Erel, Isil; Nadauld, Taylor; Stulz, René M. (Review of Financial Studies, 2014)
We provide estimates of holdings of highly rated securitization tranches of U.S. bank holding companies before the credit crisis and evaluate hypotheses that have been advanced to explain them. Whereas holdings exceeded Tier 1 capital for some large banks, they were economically trivial for the typical bank. Banks with high holdings were not riskier before the crisis using conventional measures, but they performed poorly during the crisis. We find that holdings of highly rated tranches were correlated with a bank’s securitization activity. Theories unrelated to the securitization activity, such as “bad incentives ” or “bad risk management, ” are not supported in the data. (JEL G01, G21) Holdings of highly rated tranches of securitizations held by U.S. banks were at the heart of the financial crisis of 2007–2008. At least in the early phases of the crisis, the bulk of the assets that were considered to have become toxic by many observers were these securities with subprime and alt-A mortgage collateral. Losses in value led banks to have low capital and forced them to raise more capital, cut back on new loans, and engage in fire sales (see Brunnermeier 2009). The most visible and controversial policy initiative of the U.S. Treasury